2022
DOI: 10.1038/s41467-022-29589-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-bile acid crosstalk contributes to the rebound weight gain after calorie restriction in mice

Abstract: Calorie restriction (CR) and fasting are common approaches to weight reduction, but the maintenance is difficult after resuming food consumption. Meanwhile, the gut microbiome associated with energy harvest alters dramatically in response to nutrient deprivation. Here, we reported that CR and high-fat diet (HFD) both remodeled the gut microbiota with similar microbial composition, Parabacteroides distasonis was most significantly decreased after CR or HFD. CR altered microbiota and reprogramed metabolism, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 57 publications
2
77
0
Order By: Relevance
“…These results suggest that high serum LCA and DCA levels are associated with decreased BW. Several studies have shown that adding non-12α-hydroxylated BAs (such as LCA) can effectively improve the obesity phenotype in mice ( Wei et al, 2020 ; Li et al, 2022 ). Compared to the SSJIBL group, the serum LCA and DCA levels of rats in the BID group decreased more significantly, which may be one of the reasons why the weight loss effect in the BID group was not as great as that in the SSJIBL group.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that high serum LCA and DCA levels are associated with decreased BW. Several studies have shown that adding non-12α-hydroxylated BAs (such as LCA) can effectively improve the obesity phenotype in mice ( Wei et al, 2020 ; Li et al, 2022 ). Compared to the SSJIBL group, the serum LCA and DCA levels of rats in the BID group decreased more significantly, which may be one of the reasons why the weight loss effect in the BID group was not as great as that in the SSJIBL group.…”
Section: Discussionmentioning
confidence: 99%
“…The female cats lost 4.34% of their body weight. It is important to note that the 16.48% increasing in the average volume of waste in the fall of 2018 could not stop the weight loss of cats and the downward trend in the weight of cats continued 13 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and pharmacological interventions that targeted CYP7B1 (cytochrome P450, family 7, subfamily b, polypeptide 1), the key enzyme of synthesis and biliary excretion of bile acids, have hindered the rise in fecal bile acid excretion, altered the bacterial composition of the gut and, more importantly, regulated thermogenic responses, implying that bile acids may play a role as crucial metabolic effectors under sustained BAT (50). As mentioned above, the diet was closely associated with gut microbiota and bile acids pool (64,142). Wang et al found that HFD significantly increased the deoxycholic acid (DCA) content in faces and administration of DCA promoted M1 macrophage polarization via NF-kB/ERK/JNK signaling (145).…”
Section: Bile Acidsmentioning
confidence: 99%
“…Wang et al found that HFD significantly increased the deoxycholic acid (DCA) content in faces and administration of DCA promoted M1 macrophage polarization via NF-kB/ERK/JNK signaling (145). Li and colleagues have reported that compared with normal diet, CR decreased the conjugated non-12a-hydroxylated (12OH) BAs, such as tauro-b-muricholic acid (TbMCA), tauro-w-muricholic acid (TwMCA), tauroursodeoxycholic acid (TUDCA), and taurochenodeoxycholic acid (TCDCA) (64). Interestingly, the gut microbiota will shift towards favoring bacteria that can harvest energy more efficiently during CR.…”
Section: Bile Acidsmentioning
confidence: 99%